Determination of putative vacuolar proteases, PEP4 and PRB1 in a novel yeast expression host Meyerozyma Guilliermondii strain SO using bioinformatics tools - Lorrine, Okojie Eseoghene; Rahman, Raja Noor Zaliha Raja Abd; Joo, Shun Tan; Raja Khairuddin, Raja Farhana; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Universiti Putra Malaysia Press, 2022)
Meyerozyma guilliermondii strain SO, a newly isolated yeast species from spoilt orange, has been used as a host to express the recombinant proteins using methylotrophic yeast promoters. However, as a novel yeast expression system, the vacuolar proteases of this yeast have not been determined, which may have contributed to the low level of heterologous protein secretions. Thus, this study aimed to determine intra- and extracellular proteolytic activity and identify the putative vacuolar proteases using bioinformatics techniques. A clear zone was observed from the nutrient agar skimmed milk screening plate. Proteolytic activity of 117.30 U/ml and 75 U/ml were obtained after 72 h of cultivation for both extracellular and intracellular proteins, respectively. Next, the Hidden Markov model (HMM) was used to detect the presence of the vacuolar proteases (PEP4 and PRB1) from the strain SO proteome. Aspartyl protease (PEP4) with 97.55% identity to Meyerozyma sp. JA9 and a serine protease (PRB1) with 70.91% identity to Candida albicans were revealed. The homology with other yeast vacuolar proteases was confirmed via evolutionary analysis. PROSPER tool prediction of cleavage sites postulated that PEP4 and PRB1 might have caused proteolysis of heterologous proteins in strain SO. In conclusion, two putative vacuolar proteases (PEP4 and PRB1) were successfully identified in strain SO. Further characterization can be done to understand their specific properties, and their effects on heterologous protein expression can be conducted via genome editing.